Efektivitas pada Program Aplikasi Kimia Farma Employe Service Technology (KIFEST) dalam Meningkatkan Kinerja Karyawan di PT Kimia Farma Tbk Unit RnD - Soleh, Agus Rahmat; Gunawan, Gunawan (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is to determine the effectiveness of the Chemical Application Program of Kimia Farma Employe Service Technology (KIFEST) in enhancing the performance of employees in the RnD Unit of PT Kimia Farma Tbk. Qualitative data analysis was employed, including observation and surveys. Employees from the RnD Unit who used KIFEST were the respondents. The research findings indicate that the implementation of KIFEST enhances task efficiency and effectiveness, team collaboration, and information access. Adequate training, management support, and user-friendly interfaces were also identified as crucial components in improving the adoption and effectiveness of KIFEST. This study enhances our understanding of the influence of the KIFEST Application Program on a specific research environment. The findings of this research can assist PT Kimia Farma Tbk in optimizing and enhancing the utilization of KIFEST to improve employee performance in the RnD Unit. Keywords: Effectiveness, Employee Performance, Kimia Farma Application, KIFEST.